2013
DOI: 10.4085/1062-6050-48.3.16
|View full text |Cite
|
Sign up to set email alerts
|

Two- and 3-Dimensional Knee Valgus Are Reduced After an Exercise Intervention in Young Adults With Demonstrable Valgus During Squatting

Abstract: Context: Two-dimensional (or medial knee displacement [MKD]) and 3-dimensional (3D) knee valgus are theorized to contribute to anterior cruciate ligament injuries. However, whether these displacements can be improved in the doublelegged squat (DLS) after an exercise intervention is unclear.Objective: To determine if MKD and 3D knee valgus are improved in a DLS after an exercise intervention.Design: Randomized controlled clinical trial. Setting: Research laboratory. Patients or Other Participants: A total of 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 44 publications
2
61
0
Order By: Relevance
“…Previous investigators have utilized landings and squats to assess lower extremity biomechanics associated with ACL loading and injury risks (Ali et al, 2013;Bell et al, 2013;Hewett et al, 2005;Lyle et al, 2014;Nguyen et al, 2011;Padua, 2012;Padua et al, 2012;Stensrud et al, 2011). In the current study, the differences and correlations for five biomechanical variables were identified during a single-leg landing, a single-leg squat, a double-leg landing, and a double-leg squat.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous investigators have utilized landings and squats to assess lower extremity biomechanics associated with ACL loading and injury risks (Ali et al, 2013;Bell et al, 2013;Hewett et al, 2005;Lyle et al, 2014;Nguyen et al, 2011;Padua, 2012;Padua et al, 2012;Stensrud et al, 2011). In the current study, the differences and correlations for five biomechanical variables were identified during a single-leg landing, a single-leg squat, a double-leg landing, and a double-leg squat.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, it is valuable to evaluate lower extremity biomechanics during single-leg landings. In addition, double-leg squats (Bell, Oates, Clark, & Padua, 2013;Padua, Bell, & Clark, 2012) and single-leg squats (Nguyen, Shultz, Schmitz, Luecht, & Perrin, 2011;Stensrud, Myklebust, 2 M.R. Donohue et al Kristianslund, Bahr, & Krosshaug, 2011) have been used to assess lower extremity biomechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Collecting bilateral data would demonstrate whether stance width changed between conditions. We examined gluteus medius activation as a factor related to knee abduction without including other factors such as ankle muscles and ankle motion (Bell et al, 2013;Padua et al, 2012aPadua et al, , 2012b. Only one resistance band and one band placement were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…it might be an equally important factor that weak buttocks are usually coupled with the presence of a stiff ankle and lack of dorsiflexion, where the foot's upward movement to the shin in weight-bearing exercises is limited (30). This subsequently forces the foot to pronate in order to gain range while in the squatting position (2,3). These impacting factors will be revisited in my next article of the series about the ankle complex.…”
Section: Introductionmentioning
confidence: 99%